Pre-dispersal acorn predation in mixed oak forests: interspecific differences are driven by the interplay among seed phenology, seed size and predator size - ESPELTA, JOSEP M.; Bonal, Raul; Sánchez-Humanes, Belén (Journal of Ecology, 2009)
1. Pre-dispersal seed predation (PSP) often occurs in multi-host–predator systems (e.g. several plant species exposed to a common array of granivorous insects). However, whether the interaction among seed phenology, seed size and predator size accounts for interspecific differences in PSP remains elusive. 2. We studied PSP in a mixed-oak forest with two oaks (the larger-seeded Quercus humilis and the smaller-seeded Q. ilex), both depredated by two acorn weevils (the smaller Curculio glandium and the larger C. elephas). We intensively monitored acorn production and infestation phenology and we identified the weevil species depredating acorns by means of DNA taxonomy. 3. The minimum acorn size required for infestation was lower for C. glandium than for C. elephas, in accordance with their different body sizes. This resulted in an earlier infestation phenology in C. glandium and the ability of this species to infest both smaller and larger acorns. Above a minimum acorn size threshold, no selection for larger acorns by weevils was observed. 4. Initial acorn crop size was similar in the two oaks. Nonetheless, the earlier acorn phenology and the production of larger acorns in Q. humilis favoured the earlier infestation by C. glandium and the predation by both small and large weevils. Smaller acorns of Q. ilex almost excluded infestation by the larger C. elephas. 5. Although larger acorns of Q. humilis could better survive infestation (preserve the embryo), higher PSP in this species finally resulted in a lower mature acorn crop size than in Q. ilex. 6. Synthesis. In a multi-host–predator system, smaller-seeded species may benefit from a reduced PSP because they exclude larger granivorous insects, but also by means of a ‘free-rider effect’, if larger-seeded heterospecifics earlier reach a critical size to be depredated. These results also highlight the benefits of a small body size in granivorous insects to depredate seeds earlier and to forage on a wider range of seed sizes. Whether the advantage of ‘being small’ in this antagonistic plant–animal interaction is offset by other processes, or whether it results in a pressure towards seed and insect size reduction, deserves further attention.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Curculio elephas; Curculio glandium; Mediterranean oak forests; multi-host–predator system; Quercus humilis; Quercus ilex; seed ecology; seed satiation; species coexistence

Pre-dispersal acorn predation in mixed oak forests: interspecific differences are driven by the interplay among seed phenology, seed size and predator size - Espelta, Josep M; Bonal, Raul; Sánchez-Humanes, Belén (Journal of Ecology, 2009)
1. Pre-dispersal seed predation (PSP) often occurs in multi-host–predator systems (e.g. several plant species exposed to a common array of granivorous insects). However, whether the interaction among seed phenology, seed size and predator size accounts for interspecific differences in PSP remains elusive. 2. We studied PSP in a mixed-oak forest with two oaks (the larger-seeded Quercus humilis and the smaller-seeded Q. ilex), both depredated by two acorn weevils (the smaller Curculio glandium and the larger C. elephas). We intensively monitored acorn production and infestation phenology and we identified the weevil species depredating acorns by means of DNA taxonomy. 3. The minimum acorn size required for infestation was lower for C. glandium than for C. elephas, in accordance with their different body sizes. This resulted in an earlier infestation phenology in C. glandium and the ability of this species to infest both smaller and larger acorns. Above a minimum acorn size threshold, no selection for larger acorns by weevils was observed. 4. Initial acorn crop size was similar in the two oaks. Nonetheless, the earlier acorn phenology and the production of larger acorns in Q. humilis favoured the earlier infestation by C. glandium and the predation by both small and large weevils. Smaller acorns of Q. ilex almost excluded infestation by the larger C. elephas. 5. Although larger acorns of Q. humilis could better survive infestation (preserve the embryo), higher PSP in this species finally resulted in a lower mature acorn crop size than in Q. ilex. 6. Synthesis. In a multi-host–predator system, smaller-seeded species may benefit from a reduced PSP because they exclude larger granivorous insects, but also by means of a ‘free-rider effect’, if larger-seeded heterospecifics earlier reach a critical size to be depredated. These results also highlight the benefits of a small body size in granivorous insects to depredate seeds earlier and to forage on a wider range of seed sizes. Whether the advantage of ‘being small’ in this antagonistic plant–animal interaction is offset by other processes, or whether it results in a pressure towards seed and insect size reduction, deserves further attention.
Keywords: Curculio elephas; Curculio glandium; Mediterranean oak forests; multi-host–predator system; Quercus humilis; Quercus ilex; seed ecology; seed satiation; species coexistence